Pengaruh Promosi, Kualitas Perlayanan Dan Citra Perusahaan Terhadap Volume Penjualan - I Ketut Suardika; Ni Kadek Anik Krisma Dewi (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The study aims to determine the effect of promotion, service quality and corporate image on sales volume at PT Bintang Sidoraya Buleleng Regency. The technique used in this study is a questionnaire with a measuring instrument in the form of a rating scale of 1-5 and the determination of the sample in this study using the slovin formula, namely as many as 65 customer stores from PT Bintang Sidoraya Buleleng Regency. The data analysis techniques used are Classical Assumption Test analysis, Data Description Analysis, Multiple Linear Regression Analysis, Coefficient of Determination Test (R2), Simultaneous Significance Test (F Test), Individual Significance Test (T Test), using computer program assistance (SPSS). ) Version 26.00 for Windows. The results of the analysis show that promotion has a significant positive effect on sales volume with the result (2.892) with a t-count value greater than t-table (1.670). Service quality has a significant positive effect on sales volume with the result (4,742) with a value greater than t-table (1,670). Company image has a significant positive effect on sales volume with the result (5.416) with a t-count value greater than t-table (1.670). Keywords: Promotion, Service Quality, Company Image, Sales Volume